Логістичний менеджмент у торговельному підприємництві: від оптимізації витрат до розвитку професійної компетентності - Семикіна, М. В.; Нісфоян, С. С.; Semykina, M.; Nisfoyan, S. (НТУ «ХПІ», 2025)
Стаття присвячена розробці теоретико-методичних засад вдосконалення логістичного менеджменту в контексті оптимізації витрат та підвищення професійної компетентності фахівців. Розкрито сутність логістичного менеджменту. Визначено та обґрунтовано фактори його розвитку на початку XXI століття: розповсюдження електронної комерції; глобалізація логістичних мереж; розвиток інформаційних технологій; підвищення вимог споживачів; увага до екологічності; акцент на гнучкості та швидкості реагування. Проаналізовано теоретичні та практичні аспекти управління витратами, зокрема: концепції розвитку логістичного менеджменту; концепції оптимізації витрат; підходи до класифікації логістичних витрат; методи обліку та аналізу; концепції оптимізації витрат; вплив факторів на витрати. Розкрито існуючі підходи до професійного розвитку логістичних кадрів, формування ключових компетенцій в умовах цифрової трансформації та євроінтеграції. Виявлено та систематизовано основні проблеми логістичного менеджменту в Україні, які особливо загострилися в умовах воєнних дій. Серед них: розрізненість ланцюгів поставок, неефективне управління запасами, високі транспортні витрати, недостатній рівень цифровізації та дефіцит кваліфікованих кадрів. Обґрунтовано напрями вдосконалення логістичного менеджменту, що включають інтеграцію цифрових платформ, впровадження сучасних концепцій управління запасами та транспортом, перехід до «зеленої» логістики, автоматизацію складів та розвиток професійної компетентності персоналу через навчання роботі з новітніми технологіями та європейськими стандартами та інші. Для поліпшення логістичного менеджменту рекомендовано підвищувати професійну компетентність фахівців торговельних компаній за рахунок: навчання менеджерів роботі з інтегрованими системами SCM, тренінгів з прогнозування попиту та управління запасами, підготовки фахівців з аналітики транспортних процесів, курсів з екологічних стандартів ЄС, партнерства із закладами вищої освіти для створення практико-орієнтованих програм, навчання роботі з IoT, Big Data, блокчейн-технологіями, тренінгів з антикризового управління та адаптації до змін. Доведено, що інтеграція оптимізації витрат і розвитку професійної компетентності стає необхідним елементом успішного функціонування логістичних систем сучасних підприємств. Для торговельного підприємництва це супроводжується формуванням низки переваг, зокрема дозволяє забезпечити: економічні вигоди та конкурентоспроможність торговельних компаній; підвищення якості обслуговування клієнтів; професійний розвиток персоналу та впровадження інновацій; адаптацію торговельної компанії, її логістики до сучасних викликів. Визначено, що для підвищення ефективності функціонування логістичних систем торговельних підприємств України в умовах економічної нестабільності, євроінтеграції та післявоєнного відновлення критично важливим є інтегрований підхід, що поєднує впровадження стратегій оптимізації витрат з системним розвитком професійної компетентності логістичних фахівців, здатних ефективно застосовувати сучасні технології та адаптуватися до нових викликів. The article is dedicated to developing theoretical and methodological foundations for improving logistics management in the context of cost optimization and enhancing the professional competence of specialists. Based on the generalization and development of scientific thought, logistics management is proposed to be interpreted as a comprehensive process of planning, organizing, managing, and controlling the flow of materials, information, and finances from the point of origin to the point of consumption with the aim of satisfying consumer needs in the most efficient and economical way. The essence of logistics management is explored, and the factors driving its development in the early 21st century are identified and substantiated: the proliferation of e-commerce; globalization of logistics networks; advancements in information technologies; rising consumer demands; focus on sustainability; and emphasis on flexibility and rapid response. Theoretical and practical aspects of cost management are analyzed, including: concepts of logistics management development; cost optimization frameworks; approaches to classifying logistics costs; accounting and analysis methods; the impact of external factors on costs; and strategies for cost reduction. Existing approaches to the professional development of logistics personnel, the formation of key competencies in the context of digital transformation and European integration, are also examined. The shortcomings of domestic practices in personnel professional development within the logistics sector have been identified. Such development often boils down to formal upskilling and retraining programs that frequently fail to keep pace with rapid changes in the logistics industry and market demands. There's often a lack of a systemic approach to identifying training needs, developing individual career paths, and evaluating the effectiveness of the training provided. A significant portion of the training focuses on theoretical knowledge, while practical skills, especially concerning the implementation of modern technologies and cost optimization in logistics management, remain underdeveloped. The study identifies and systematizes key challenges facing logistics management in Ukraine, which have intensified during wartime. These include fragmented supply chains, inefficient inventory management, high transportation costs, insufficient digitalization, and a shortage of qualified personnel. Directions for improving logistics management are proposed, such as integrating digital platforms, adopting modern inventory and transportation management concepts, transitioning to "green" logistics, warehouse automation, and enhancing staff competence through training in cutting-edge technologies and EU standards. To strengthen logistics management, recommendations emphasize upskilling professionals in trade companies via: training managers in integrated SCM systems, demand forecasting and inventory management workshops, analytics for transport processes, EU environmental standards courses, partnerships with universities to develop practice-oriented programs, training in IoT, Big Data, blockchain technologies, and crisis management. The research highlights a critical contradiction between Ukrainian trade enterprises’ urgent need to optimize logistics costs and the insufficient professional competence of specialists to implement innovative approaches effectively, particularly in the context of European integration and postwar recovery. Statistical evidence confirms that the existing deficit in logistics management expertise leads to inefficient resource allocation and increased operational risks. During wartime, the primary task for logistics management is ensuring supply chain resilience through measures such as diversifying suppliers, developing alternative routes (accounting for security risks), collaborating with reliable carriers, creating strategic reserves of critical goods, and utilizing real-time cargo tracking technologies, GPS monitoring, and Transportation Management Systems (TMS). Postwar logistics priorities include rebuilding infrastructure, establishing new logistics networks, strategic demand forecasting aligned with shifting consumer behavior, revising logistics strategies to align with European integration, and attracting foreign investment. Cost optimization and professional development of logistics personnel remain central to sustaining trade enterprises. The study demonstrates that integrating cost optimization with professional competence development is essential for the successful functioning of modern logistics systems. For trade enterprises, this synergy yields economic benefits, competitive advantage, improved customer service, innovation adoption, and adaptability to contemporary challenges. In conclusion, enhancing the efficiency of Ukrainian trade enterprises’ logistics systems amid economic instability, European integration, and postwar recovery requires an integrated approach that combines cost optimization strategies with systematic development of logistics professionals’ competencies. These professionals must be equipped to leverage modern technologies and adapt to emerging challenges.
Logistics management in trade entrepreneurship: from cost optimization to professional competence development
Keywords: логістичний менеджмент; управління витратами; професійний розвиток; оптимізація; стратегії; професійні компетентності; логістичні фахівці; інтегрований підхід; logistics management; cost management; professional development; optimization; strategies; professional competencies; logistics specialists; integrated approach